Phylogeography of the woolly mammoth (Mammuthus primigenius) in the Minusinsk Depression of southern Siberia in the Late Pleistocene - S. A. Modina; M. A. Kusliy; D. G. Malikov; A. S. Molodtseva (Вавиловский журнал генетики и селекции)
To date, a number of studies have been published on the phylogenetics of woolly mammoths (Mammuthus primigenius), ranging from analyses of parts of the mitochondrial genome to studies of complete nuclear genomes. However, until recently nothing was known about the genetic diversity of woolly mammoths in southern Siberia, in the Minusinsk Depression in particular. Within the framework of this eﬀort, libraries for high-throughput sequencing of seven bone samples of woolly mammoths were obtained, two-round enrichment using biotinylated probes of modern mtDNA of Elephas maximus immobilised on magnetic microspheres and sequencing with subsequent bioinformatic analysis were carried out. Phylogenetic reconstructions showed the presence of all studied mammoths in clade I, which expanded its range. The assignment of mammoth mitotypes in the Minusinsk Depression to diﬀerent clusters within clade I may indicate a sufficiently high diversity of their gene pool. Phylogeographic reconstructions revealed a genetic proximity of mitochondrial lineages of Late Pleistocene mammoths of the Minusinsk Depression and other regions of eastern Siberia and estimated their divergence time in the range of 100–150 thousand years ago, which indicates active migrations of woolly mammoths over vast territories of eastern Siberia in the late Middle Pleistoceneearly Late Pleistocene.